Africa's Rising Exposure to China : How Large Are Spillovers Through Trade? - Drummond, Paulo (IMF Working Papers; Working Paper ;, 2013)
The rapid growth in China's domestic investment in recent decades has generated a large appetite for global goods, including from sub-Saharan Africa (SSA). This paper estimates the impact of changes in China's investment growth on SSA's exports. Although rising trading links with China have allowed African countries to diversify their export base across countries, away from advanced economies, they have also led SSA countries to become more susceptible to spillovers from China. Based on panel data analysis, a 1 percentage point increase (decline) in China's domestic investment growth is associated with an average 0.6 percentage point increase (decline) in SSA countries' export growth. This impact is larger for resource-rich countries, especially oil exporters. These effects could be mitigated, however, to the extent that countries can reorient their exports.